Pengaruh Struktur Modal, Internal Control dan Firm Size terhadap Tingkat Laba pada PT. Industri Kapal Indonesia Makassar - Ibrahim H. Ahmad; Abdul Khalik; Zainal Abidin (AkMen JURNAL ILMIAH, 2022)
This study aims to determine the effect of Capital Structure, Internal Control and Company Size Partially on Profit Levels at PT. Indonesian Ship Industry Makassar. and to find out the Capital Structure, Internal Control And Company Size Simultaneously Affect The Profit Level At PT. Makassar Indonesian Ship Industry and to find out the internal variables that have a dominant influence on the level of profit at PT. Makassar Indonesian Ship Industry and to find out how much the contribution of the three research variables to the Profit Level at PT. Indonesian Ship Industry Makassar Data collection techniques used a questionnaire distributed to 35 respondents as a sample. The results of the study were then processed using multiple linear regression analysis tools. The results of the t test show that partially the capital structure, internal control and firm size have a positive and significant effect on the level of profit at PT. Indonesian Ship Industry Makassar. Only the internal control variable is not significant to the level of profit earned at PT. Indonesian Ship Industry Makassar. Based on the f test shows that the capital structure, internal control and firm size have a positive and significant effect on the level of profit at PT. Indonesian Ship Industry Makassar.. The contribution of the three research variables is 61.7%. The remaining 38.3 is influenced by other variables not examined in this study